Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine which of the given quadratic functions has zeros at [tex]\( x = 6 \)[/tex] and [tex]\( x = -4 \)[/tex], let's analyze each function step by step.
### Quadratic Function Zeros
A quadratic function [tex]\( f(x) \)[/tex] has the form:
[tex]\[ f(x) = a(x - r_1)(x - r_2) \][/tex]
where [tex]\( r_1 \)[/tex] and [tex]\( r_2 \)[/tex] are the zeros (roots) of the function. Given zeros are [tex]\( r_1 = 6 \)[/tex] and [tex]\( r_2 = -4 \)[/tex]. Thus, the function can be written as:
[tex]\[ f(x) = a(x - 6)(x + 4) \][/tex]
where [tex]\( a \)[/tex] is a non-zero constant.
### Analysis of Each Choice
Let’s check each function one by one to see which has the zeros at 6 and -4.
#### Choice A:
[tex]\[ f(x) = (x - 6)(x + 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 - 6)(6 + 4) = 0 \cdot 10 = 0 \][/tex]
- At [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = (-4 - 6)(-4 + 4) = (-10) \cdot 0 = 0 \][/tex]
Since [tex]\( f(x) = 0 \)[/tex] at both [tex]\( x = 6 \)[/tex] and [tex]\( x = -4 \)[/tex], function A is a candidate.
#### Choice B:
[tex]\[ f(x) = (x + 6)(x - 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 + 6)(6 - 4) = 12 \cdot 2 = 24 \neq 0 \][/tex]
Since [tex]\( f(x) \neq 0 \)[/tex] at [tex]\( x = 6 \)[/tex], function B is not a candidate.
#### Choice C:
[tex]\[ f(x) = (x - 6)(x - 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 - 6)(6 - 4) = 0 \cdot 2 = 0 \][/tex]
- At [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = (-4 - 6)(-4 - 4) = (-10)(-8) = 80 \neq 0 \][/tex]
Since [tex]\( f(x) \neq 0 \)[/tex] at [tex]\( x = -4 \)[/tex], function C is not a candidate.
#### Choice D:
[tex]\[ f(x) = (x + 6)(x + 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 + 6)(6 + 4) = 12 \cdot 10 = 120 \neq 0 \][/tex]
Since [tex]\( f(x) \neq 0 \)[/tex] at [tex]\( x = 6 \)[/tex], function D is not a candidate.
### Conclusion
The function [tex]\( f(x) = (x - 6)(x + 4) \)[/tex] is the only one that has zeros at [tex]\( x = 6 \)[/tex] and [tex]\( x = -4 \)[/tex].
Thus, the correct choice is:
[tex]\[ \boxed{A} \][/tex]
### Quadratic Function Zeros
A quadratic function [tex]\( f(x) \)[/tex] has the form:
[tex]\[ f(x) = a(x - r_1)(x - r_2) \][/tex]
where [tex]\( r_1 \)[/tex] and [tex]\( r_2 \)[/tex] are the zeros (roots) of the function. Given zeros are [tex]\( r_1 = 6 \)[/tex] and [tex]\( r_2 = -4 \)[/tex]. Thus, the function can be written as:
[tex]\[ f(x) = a(x - 6)(x + 4) \][/tex]
where [tex]\( a \)[/tex] is a non-zero constant.
### Analysis of Each Choice
Let’s check each function one by one to see which has the zeros at 6 and -4.
#### Choice A:
[tex]\[ f(x) = (x - 6)(x + 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 - 6)(6 + 4) = 0 \cdot 10 = 0 \][/tex]
- At [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = (-4 - 6)(-4 + 4) = (-10) \cdot 0 = 0 \][/tex]
Since [tex]\( f(x) = 0 \)[/tex] at both [tex]\( x = 6 \)[/tex] and [tex]\( x = -4 \)[/tex], function A is a candidate.
#### Choice B:
[tex]\[ f(x) = (x + 6)(x - 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 + 6)(6 - 4) = 12 \cdot 2 = 24 \neq 0 \][/tex]
Since [tex]\( f(x) \neq 0 \)[/tex] at [tex]\( x = 6 \)[/tex], function B is not a candidate.
#### Choice C:
[tex]\[ f(x) = (x - 6)(x - 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 - 6)(6 - 4) = 0 \cdot 2 = 0 \][/tex]
- At [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = (-4 - 6)(-4 - 4) = (-10)(-8) = 80 \neq 0 \][/tex]
Since [tex]\( f(x) \neq 0 \)[/tex] at [tex]\( x = -4 \)[/tex], function C is not a candidate.
#### Choice D:
[tex]\[ f(x) = (x + 6)(x + 4) \][/tex]
- At [tex]\( x = 6 \)[/tex]:
[tex]\[ f(6) = (6 + 6)(6 + 4) = 12 \cdot 10 = 120 \neq 0 \][/tex]
Since [tex]\( f(x) \neq 0 \)[/tex] at [tex]\( x = 6 \)[/tex], function D is not a candidate.
### Conclusion
The function [tex]\( f(x) = (x - 6)(x + 4) \)[/tex] is the only one that has zeros at [tex]\( x = 6 \)[/tex] and [tex]\( x = -4 \)[/tex].
Thus, the correct choice is:
[tex]\[ \boxed{A} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.